The prevalence of common sleep disorders in young adults: a descriptive population-based study. Issue 10 (13th April 2020) - McArdle, Nigel; Ward, Sarah V; Bucks, Romola S; Maddison, Kathleen; Smith, Anne; Huang, Rae-Chi; Pennell, Craig E; Hillman, David R; Eastwood, Peter R
Abstract: Sleep disorders in adults are associated with adverse health effects including reduced quality of life and increased mortality. However, there is little information on sleep disorders in young adults. A cross-sectional observational study was undertaken in 1, 227 young adults participating in the Western Australian Pregnancy (Raine) Study (2012–2014) to describe the prevalence of common sleep disorders. In-laboratory polysomnography (PSG) and validated survey methods were used, including the Epworth Sleepiness Scale, Pittsburgh Sleep Symptom Questionnaire-Insomnia, and International Restless Legs Syndrome Study Group criteria. A total of 1, 146 participants completed a core questionnaire, 1, 051 completed a sleep-focused questionnaire and 935 had analyzable PSG data. Participants had a mean age of 22.2 years and female to male ratio of 1.1 to 1. The respective sleep disorder prevalences in females and males were: obstructive sleep apnea (OSA) (apnea-hypopnea index [AHI]: ≥5 events/hour) 14.9% (95% CI: 11.8–18.5) and 26.9% (95% CI: 22.9–31.2); chronic insomnia, 19.3% (95% CI: 16.7–23.9) and 10.6% (95% CI: 8.3–13.9); restless legs syndrome, 3.8% (95% CI: 2.4–5.6) and 1.9% (95% CI: 0.9–3.4); and abnormal periodic leg movements during sleep (>5 movements/hour), 8.6% (95% CI: 6.3–11.5) and 9.6% (95% CI: 7.1–12.7). There were statistically significant differences in prevalence between sexes for OSA and insomnia, which persisted after adjustment for body mass index and education. In those with complete data on all sleep-related assessments ( n = 836), at least one sleep disorder was present in 41.0% of females and 42.3% of males. Sleep disorders are very common in young adults. Health practitioners should be aware of these high prevalences, as early identification and treatment can improve quality of life and may reduce later morbidity and mortality.